2022
DOI: 10.21037/jtd-22-334
|View full text |Cite
|
Sign up to set email alerts
|

Time since primary transplant and poor functional status predict survival after redo lung transplant

Abstract: Background: In previous studies, lower functional status measured by Karnofsky Performance Status (KPS) correlated with worse survival after redo lung transplant. We hypothesize that combining reduced functional status and time from primary lung transplant will correlate with the etiology of lung allograft failure after primary lung transplant and more accurately predict survival after redo lung transplant.Methods: This retrospective study was approved by University of Minnesota Institutional Review Board. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recipient factors such as preoperative mechanical ventilation, mechanical circulatory support, LAS, and time from primary transplant are all known predictors of poor survival after retransplant. [7][8][9][10] In addition, there is a known association between poor functional status and adverse outcomes after lung transplantation, including inhospital and 1-year mortality, transplant encounter length of stay, and likelihood of finding paid employment after the operation. [11][12][13][14] The Karnofsky Performance Status (KPS), initially developed to quantify the functional status of cancer patients after an intervention, is a functional metric collected pre-transplant, at time of match, and posttransplant follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipient factors such as preoperative mechanical ventilation, mechanical circulatory support, LAS, and time from primary transplant are all known predictors of poor survival after retransplant. [7][8][9][10] In addition, there is a known association between poor functional status and adverse outcomes after lung transplantation, including inhospital and 1-year mortality, transplant encounter length of stay, and likelihood of finding paid employment after the operation. [11][12][13][14] The Karnofsky Performance Status (KPS), initially developed to quantify the functional status of cancer patients after an intervention, is a functional metric collected pre-transplant, at time of match, and posttransplant follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Recipient factors such as preoperative mechanical ventilation, mechanical circulatory support, LAS, and time from primary transplant are all known predictors of poor survival after retransplant 7–10 . In addition, there is a known association between poor functional status and adverse outcomes after lung transplantation, including in‐hospital and 1‐year mortality, transplant encounter length of stay, and likelihood of finding paid employment after the operation 11–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown its predictive value for outcomes after both primary and redo LTx ( 1 , 2 ). Aggarwal and colleagues ( 3 ) addressed a potential utility for preoperative functional status when analyzed against patients’ time between primary and redo LTx. Namely, when redo LTx recipients are categorized by both variables, it reveals two distinct “phenotypes” of patients with dichotomous clinical and prognostic outcomes.…”
mentioning
confidence: 99%